1990
DOI: 10.2307/1242625
|View full text |Cite
|
Sign up to set email alerts
|

Computer Use by Ohio Commercial Farmers

Abstract: Although computer technologies have evolved rapidly, farmers have been slow to adopt these technologies. This research identities factors influencing farmers' adoption of computers and the number and type of applications for which the computer is used. Ohio commercial farmers were randomly sampled and analyzed using multinomial logit techniques. Results suggest that older farmers are less likely to adopt computers, less likely to find them useful, and make fewer applications of the computer in their business. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 7 publications
9
50
1
1
Order By: Relevance
“…In this sense, conservation practices that are little known are not likely to be easily adopted, giving policy makers clear direction to instigate promotional activities. In Ohio (USA), for example, availability of information that leads to increased awareness and knowledge was one of the most popularly cited requirements by farmers for successful uptake of a conservation practice (Batte et al 1990). Langholz et al (2000a), in their study of landowners participating and not participating in Costa Rica's Private Wildlife Refuge Programme, found a substantial information gap existed, which if breached would lead to easy and quick uptake.…”
Section: Knowledge and Awareness Of The Programme And Its Relevance mentioning
confidence: 99%
“…In this sense, conservation practices that are little known are not likely to be easily adopted, giving policy makers clear direction to instigate promotional activities. In Ohio (USA), for example, availability of information that leads to increased awareness and knowledge was one of the most popularly cited requirements by farmers for successful uptake of a conservation practice (Batte et al 1990). Langholz et al (2000a), in their study of landowners participating and not participating in Costa Rica's Private Wildlife Refuge Programme, found a substantial information gap existed, which if breached would lead to easy and quick uptake.…”
Section: Knowledge and Awareness Of The Programme And Its Relevance mentioning
confidence: 99%
“…Results also suggest that the educational level of the farm operator, farm size, farm diversification, off-farm income, off-farm investments, and regional location of the farm significantly affect the number of Internet applications used. Batte (2004) found that about 80 percent of computer-adopting Ohio farmers also used the Internet for online business such as financial transactions, purchasing inputs, and marketing outputs. In fact, Internet tasks combined to be one of the three most important computer tasks identified by 73.5 percent of computer-adopting farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on technology adoption suggests that operators of larger farms and farmers with greater formal education are more likely to be early adopters (Rogers 1983). For high technology such as computers and information technologies, younger farmers also are often found to be early adopters (Batte, Jones, andSchnitkey 1990, Putler andZilberman 1988). We included interactions of operator age, education (post-high school = 1), and farm size (gross sales) with both ∆OnlineStore and ∆NationalStore.…”
Section: Conjoint Model Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies show that personal and business characteristics affect the computer and internet use of farmers (Alvarez and Nuthall, 2006;Amponsah, 1995;Batte et al, 1990;Batte, 2005;Carrer et al, 2017;Gloy and Akridge, 2000;Huffman and Mercier, 1991;Jarvis, 1990;Mishra and Park, 2005;Ortmann et al, 1994;Putler and Zilberman, 1988;Woodburn et al, 1994).…”
Section: Sociodemographic and Business Characteristics In E-commercementioning
confidence: 99%